Leveraging Personal Extreme Programming for Developing an Online Registration System - Tya Rahma Shani; Sigit Mintoro; Ngajiyanto Ngajiyanto (LPPM Universitas Islam 45 Bekasi, 2024)
The development of an online admission system in schools is expected to make new student admissions more transparent, effective, and efficient. With the adoption of this technology, schools can be more efficient in managing admission lists, providing information to prospective students and parents, and speeding up the admission selection process. SMA MANBAUL ULUM is a private school that still uses a manual new student registration and admission system, where prospective students must come directly to the school to register themselves causing errors in student data and the loss of important student registration documents. The author examines the new student registration system running at Sma Manbaul Ulum Gayau Sakti Seputih Agung and proposes a web-based new student admission system that is expected to solve these problems. The author uses the Personal Extreme Programming method to design the system in this research.